RANCANG BANGUN SISTEM INFORMASI PENJUALAN ALAT PANCING DI KOPERASI NELAYAN BATAM MADANI - Sijabat, Aditiya Riyanto; Erlin Elisa (Computer Science and Industrial Engineering, 2024)
The Batam Madani Fishermen's Cooperative is a business that markets equipment, namely equipment for fishing, including fishing rods, hooks, floats, winches, bait and others. With the increasingly complex development of the fishing equipment business, this business requires a computerized system for marketing its fishing equipment. The Batam Madani Fishermen's Cooperative, which until now is still marketing fishing equipment manually, is the process of recording it in a ledger and inputting it into the Microsoft Excel application, which often creates difficulties in providing information in the form of reports on the types of fishing equipment and incoming fishing equipment, fishing equipment that has not been sold, and stock records by interested parties. Another visible satisfaction is that buyers can only view or order goods by coming directly to the Fishermen's Cooperative or by looking at brochures distributed to several areas. However, these methods are considered inefficient for buyers who are far from cooperative. Therefore, a new Information System is needed that can facilitate the marketing of fishing equipment.